Clinical correlates of resilience factors in geriatric depression. (16th January 2018) - Laird, Kelsey T.; Lavretsky, Helen; Paholpak, Pattharee; Vlasova, Roza M.; Roman, Michael; St. Cyr, Natalie; Siddarth, Prabha
ABSTRACT: Background: Traditional perspectives conceptualize resilience as a trait and depression as resulting from resilience deficiency. However, research indicates that resilience varies substantially even among adults who are clinically depressed, as well as across the lifespan of an individual. Few studies have investigated resilience in depression, and even fewer have examined resilience in depressed older adults. Methods: Three hundred thirty-seven adults ≥60 years with major depressive disorder completed the Connor–Davidson Resilience Scale (CD-RISC) and measures of mental health, quality of life (QOL), and medical comorbidity. Exploratory factor analysis was used to explore the factor structure of the CD-RISC. Correlations and general linear models were used to examine associations between resilience and other variables. Results: The rotated component matrix indicated a four-factor model. Sorting of items by highest factor loading revealed constructs associated with (1) grit, (2) active coping self-efficacy, (3) accommodative coping self-efficacy, and (4) spirituality. Resilience was significantly correlated with increased age, lower cognitive functioning, greater cerebrovascular risk, and greater medical comorbidity. Resilience was negatively associated with mental health symptoms (depression, apathy, and anxiety) and positively associated with QOL. The final optimal model identified less depression, less apathy, greater medical comorbidity, higher QOL, and minority (non-White) race as factors that significantly explained variability in resilience. Conclusions: Resilience was significantly associated with a range of mental health constructs in a sample of older adults with depression. Future clinical trials and dismantling studies may help determine whether interventions targeting grit, active coping, accommodative coping, and spirituality can increase resilience and help prevent and treat depression in older adults.